2017
DOI: 10.5897/ajmr2016.8095
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of petroleum product emulsifying Pseudomonas strains from a generating set fuel tank

Abstract: This study characterized microbial strains isolated from diesel fuel samples collected from the tank of a generating set at the Institute of Research for Development in Pointe-Noire (Congo). Two bacterial isolates (G2 and G3) were distinguished by their color on agar plates and were characterized by their API 20E biochemical profiles and by 16S rRNA gene sequencing. The phenotypic properties of these isolates were consistent with their assignment to the genus Pseudomonas. Comparative 16S rRNA gene sequence ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…This species is therefore worth investigating for hydrocarbon bioremediation. Other isolates obtained in this study belonged to Pseudomonas , a genus renowned for its hydrocarbon degradation capabilities, also via the synthesis of biosurfactants [ 9 , 12 , 39 ]. Particularly, we report the isolation of Pseudomonas guguanensis strain SGPP2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This species is therefore worth investigating for hydrocarbon bioremediation. Other isolates obtained in this study belonged to Pseudomonas , a genus renowned for its hydrocarbon degradation capabilities, also via the synthesis of biosurfactants [ 9 , 12 , 39 ]. Particularly, we report the isolation of Pseudomonas guguanensis strain SGPP2.…”
Section: Discussionmentioning
confidence: 99%
“…Surfactants reduce the surface tension at the oil–water interface, thus encapsulating oil in microdroplets and consequently making it more bioavailable [ 4 ]. Micro-organisms, including bacterial genera Bacillus , Pseudomonas , Rhodococcus , Acinetobacter , Corynebacterium , and Nocardia [ 6 , 9 , 10 , 11 ], are able to synthesize surface active agents called biosurfactants from cheap substrates, such as industrial wastes, or from carbon sources, such as oils [ 4 , 11 ]. Biosurfactants are amphiphilic molecules with hydrophilic and hydrophobic moieties that optimize the microbial uptake of petroleum hydrocarbons by increasing the contact area with the contaminants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of these species in polluted environments is due to their ability to tolerate and use pollutants as a source of carbon and energy [27]. Most of these strains have already been identified in environments polluted by hydrocarbons [10,[27][28][29]. Liang et al (2014) also identified a strain of Pseudomonas sp.…”
Section: Characterization Of Gram-bacteriamentioning
confidence: 99%
“…According to the US Environmental Protection Agency's (EPA) National Priority List, 40% of hazardous waste sites are co-contaminated with organic pollutants and heavy metals. Remediation of these sites poses a complex problem due to the mixed nature of the contaminants [10]. The ARIA database (Analyse, Recherche et Information sur les Accidents -Analysis, Research and Information on Accidents), operated by the French Ministry of Ecology, Sustainable Development and Town and Country Planning, has recorded accidental events in France and abroad that have or could have affected public health and safety, agriculture and the environment.…”
Section: Introductionmentioning
confidence: 99%